Failure to oxygenate during cardiopulmonary bypass; treatment options and intervention algorithm - Matte Gregory S.; Regan William L.; Gadille Sarah I.; Connor Kevin R.; Boyle Sharon L.; Fynn-Thompson Francis E. (The Journal of ExtraCorporeal Technology)
Membrane oxygenator failure remains a concern for perfusion teams. Successful outcomes for this low-frequency, high-risk intervention are predicated on having written institutional protocols for both the oxygenator change-out procedure as well as how often the procedure is practiced by staff perfusionists. A recent review of peer-reviewed journal articles, textbooks and online resources revealed a lack of a unified intervention algorithm for failure to oxygenate during cardiopulmonary bypass (CPB). While an oxygenator change-out procedure may still be considered the gold standard for a confirmed device failure, temporizing measures exist that, in select cases, can afford time to the clinical team and even obviate the need for an oxygenator change-out procedure. We now consider the venous piggyback technique sourcing blood from the venous limb of the circuit a first-line intervention to afford enhanced patient safety while the clinical team decides on required interventions when oxygenator failure presents during CPB.